Sustainable Innovation in Geotechnics: Behavior of Clay Soils Stabilized with Organic Additives and Agro-industrial By-products. - Isla Gómez, José Manuel (2026)
The stabilization of clayey soils is a persistent challenge in civil engineering due to their plasticity, low bearing capacity, and moisture-induced volumetric changes. Given the environmental and economic impacts of traditional stabilizers (cement and lime), interest has increased in organic additives — biopolymers, lignocellulosic residues, enzymes, and molasses — as more sustainable alternatives. These compounds, generally derived from plant sources or industrial by-products, interact with soil particles through physical and chemical bonds that improve compaction, enhance strength, and reduce permeability. This review synthesizes recent findings on the performance, mechanisms of action, and practical applicability of these additives in clayey soils, with an emphasis on their potential advantages over conventional stabilizers. The present review focuses on analyzing the most relevant advances concerning these types of additives, highlighting their mechanisms of action, geotechnical applicability, and the potential they offer as eco-friendly substitutes for conventional stabilizers.